The involvement of extension agent in planning, implementing and monitoring activities base on the rice check at IADA Pekan, Pahang - Mohd Hanif, Nor Latifah (2016)
Rice is the most cultivated and consumed cereal in Malaysia. In order to fulfil the rice demand for the growing population and with the rice self-sufficiency of 70%, Malaysia has to increase its rice productivity in a sufficient and sustainable manner to meet the increasing demand. Government has made many efforts such as to support a local research by MARDI to produce a new and good variety of paddy which is MR219 and also provide the Technology of Rice check by Department of Agriculture, (DOA) since 2002 as a manual and guideline to the extension agents and also respondents for their needs. The major problem is the current yield at IADA Pekan is only 2.6 mt/ha and the performance of paddy yield is not even half than the potential yield which is 10 mt/ha. Besides that, this study aimed to measure the involvement level and work performance of extension agents in objective setting, planning, implementing, and monitoring activities in transfer of technology based on Rice Check in IADA Pekan. This study was conducted in Pekan, Pahang and the selection of respondent is by using stratified randomized method. The respondents consisted of 141 respondents from 3 schemes which are Pahang Tua, Ganchong and Pulau Jawa based on yield range of 2.1-3.1 mt/ha. The data collected were analyzed by using Statistical Package for the Social Sciences (SPSS) version 21.0. In this study, three types of statistic procedure were used to analyse the data which are descriptive, correlation and regression analysis. Based on result obtained, the respondents at IADA Pekan has moderate level of practice toward rice check technology and the relationship between management function and work performance is moderate. Based on regression analysis, objective setting and monitoring activities is important and strongly influenced the work performance in IADA Pekan. So, to conclude, extension agents at IADA Pekan need to improve and focussing in objective setting, planning, implementing, and monitoring activities to achieve the aim and goal which is to get higher yield for next planting season. As a recommendation, all the respondents need to follow the Rice Check in paddy plantation and extension agents need to guide them for planning, implementing, and monitoring activities.